From correlation towards causality: modulating brain rhythms of pain using transcranial alternating current stimulation - Hohn, Vanessa D. (Pain Rep, 2019)
INTRODUCTION: Accumulating evidence suggests that neural oscillations at different frequencies and their synchrony between brain regions play a crucial role in the processing of nociceptive input and the emergence of pain. Most findings are limited by their correlative nature, however, which impedes causal inferences. OBJECTIVE: To move from correlative towards causal evidence, methods that allow to experimentally manipulate oscillatory brain activity are needed. RESULTS: Transcranial alternating current stimulation (tACS) is a noninvasive brain stimulation technique designed to modulate neural oscillations in a frequency specific manner and as such a suitable method to investigate the contribution of oscillatory brain activity to pain. Despite its appeal, tACS has been barely applied in the field of pain research. In the present review, we address this issue and discuss how tACS can be used to gather mechanistic evidence for the relationship between pain and neural oscillations in humans. CONCLUSIONS: Transcranial alternating current stimulation holds great potential for the investigation of the neural mechanisms underlying pain and the development of new treatment approaches for chronic pain if necessary methodological precautions are taken.